Justicia de género transformadora - Boesten, Jelke (2022)
Drawing on Andrea Durbach’s work around post-conflict transformative gender justice, this paper asks if criminal justice for conflict-related sexual violence (CRSV) can bring about transformative gender justice in Latin America. The paper offers a comparative analysis of two judicial cases of conflict-related rape: the Sepur Zarco case in Guatemala and the Manta y Vilca case in Peru. The paper argues that domestic courts can have important transformative effects on victim-survivors, their families and on criminal justice practices for CRSV, when international standards for evidentiary practice are adhered to within the specific local context of the case in question, as was the case of Sepur Zarco. If international standards of evidentiary practice are not considered, it is much less likely that such cases are transformative, in fact, the process might do harm, as in the case of Manta y Vilca. Therefore, criminal justice processes are not by default transformative, but good practice can be important to transformative gender justice by providing redress for victim-survivors and affected communities, unsettling hierarchies and building accountability.